2013
DOI: 10.1038/nprot.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Object recognition test in mice

Abstract: The object recognition test is now among the most commonly used behavioral tests for mice. A mouse is presented with two similar objects during the first session, and then one of the two objects is replaced by a new object during a second session. The amount of time taken to explore the new object provides an index of recognition memory. As more groups have used the protocol, the variability of the procedures used in the object recognition test has increased steadily. This protocol provides a necessary standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
700
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 952 publications
(758 citation statements)
references
References 31 publications
8
700
2
11
Order By: Relevance
“…The NOR is a widely used learning and memory task, which offers no external stimuli or reinforcement (Leger et al. 2013). During day 1—familiarization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The NOR is a widely used learning and memory task, which offers no external stimuli or reinforcement (Leger et al. 2013). During day 1—familiarization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we asked whether deletion of endothelial S1pr1 and after BBB opening can affect recognition memory. For this purpose, control and S1pr1 iECKO mice were tested for the novel object recognition (NOR) task, a paradigm that is commonly used to investigate recognition memory performance (31). In this behavioral test, we found that S1pr1 iECKO mice spent significantly less time in exploring a novel object than control mice (Fig.…”
Section: Inflammatory Gene Expression and Cognitive Function In Earlymentioning
confidence: 99%
“…Equipment was set up as per Leger et al [23]. The arena was constructed from grey plastic and measured 40 x 40 cm.…”
Section: Novel Object Recognitionmentioning
confidence: 99%
“…The hole-board test was used to assess independent measures of exploratory tendency and neophobia. Novel object recognition was performed to test recognition memory with a short habituation period (5 minutes) 24 hours before the familiarisation phase [23]. An observer blinded to the animal treatment scored behaviours manually.…”
Section: Behavioural Testingmentioning
confidence: 99%